Curative response to combined targeted-immunotherapy for post-hepatectomy lymph node metastasis in sarcomatoid hepatocellular carcinoma: case report and literature review - Liu, Pan; Zhang, Song; Xin, Xiao-Ming; Jing, Min; Wen, Lie-Dong; Xiang, Xin; Liu, Shun-Hai (Frontiers in Oncology, 2025)
Sarcomatoid hepatocellular carcinoma (SHC) is an aggressive malignancy with poor therapeutic outcomes. Current evidence supports radical surgical resection as the primary treatment modality, yet it is associated with prohibitively high postoperative recurrence rates. We report the clinical course of a 66-year-old male diagnosed with SHC. A hepatic mass (4.1 × 2.7 × 4.4 cm) was incidentally detected during routine health screening. The patient underwent laparoscopic right posterior sectionectomy, with histopathological confirmation of SHC. Superior mesenteric lymphadenopathy suspicious for metastasis developed 1 month postoperatively. Prophylactic transarterial chemoembolization was initiated, followed by 6-month tyrosine kinase inhibitor (TKI) therapy, achieving disease stabilization. However, lymph nodes progression occurred after TKI discontinuation, confirming metastatic involvement. Subsequent combined therapy (a TKI and an anti-PD-1 antibody) was administered. Notably, the patient self-discontinued treatment after two cycles, yet subsequent imaging revealed complete resolution of metastatic lymphadenopathy. No additional antitumor therapy has been administered, and the patient remains recurrence-free with 18-month overall survival confirmed by recent radiographic surveillance.